A Non-Inversible Function

If a function f(x)f(x) from reals to reals satisfies that 2f(2x)f(x2)2=12f(2x)-f(x^2)^2=1 then prove that f1(x)f^{-1}(x) does not exist.

source: me

#Algebra #Functions #InverseFunction #Existence

Note by Daniel Liu
7 years ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

We basically have to prove that there exists distinctx1,x2x_1,x_2 such that f(x1)=f(x2)f(x_1)=f(x_2) because if f1(x)f^{-1}(x) does exist under this, then f1(f(x1))=x1,f1(f(x2))=x2f^{-1}(f(x_1))=x_1, f^{-1}(f(x_2))=x_2, which violates the definition of a function that f(x)f(x) corresponds to at most one value.

For this problem simply take x=0,2x=0,2 and we have it.

To elaberate, we first find a value xx such that 2x=x2=y2x=x^2=y so that we get an equation with one variable, it turns out that this would lead to only one solution for f(y)f(y) since (f(y)1)2=0f(y)=1(f(y)-1)^2=0\Rightarrow f(y)=1. Since x2=2xx^2=2x gives x=0,2x=0,2, we have f(0)=1,f(2)=1f(0)=1,f(2)=1.

Xuming Liang - 7 years ago

Log in to reply

Excellent Solution. Did not think that way!

Avineil Jain - 7 years ago

Yep, that's correct. Quite an interesting problem, until you realize that the solution is very quick and easy.

Daniel Liu - 7 years ago

for x(2-x) has two solutions 0 and 2 .. !! the values of the function is 1 for two elements in its domain i.e x=0 and 2 .. its not onto .. !

Ramesh Goenka - 7 years ago

For what domain?

Kanthi Deep - 7 years ago

Log in to reply

That's a good question to ask.

Calvin Lin Staff - 7 years ago

I think all reals works, but if you see any contradiction feel free to tell me and I can change it.

Daniel Liu - 7 years ago

Put x=2, it gives f(4)=1 . Now differentiating the given equality, 4f'(2x)-2f(x^2)f'(x^2)*2x = 0. put x=2, it gives ,f(4)=1/2 ..clearly, the function is non-invertible..

Aamir Rafiq - 7 years ago
×

Problem Loading...

Note Loading...

Set Loading...